The Association between ER, PR, HER2, and ER−/PR+ Expression and Lung Cancer Subsequent in Breast Cancer Patients: A Retrospective Cohort Study Based on SEER Database - Hong Yu Shao; Bao Tan Hao; Feng Xiao Gao (The Breast Journal)
Aims. The available research on the association between estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), ER−/PR+ status, and the occurrence of lung cancer subsequent to breast cancer in patients (referred to as BC-LuC) had been limited. Consequently, there is a need to examine whether ER, PR, HER2, and ER−/PR+ have independent correlations with the risk and outcomes of BC-LuC, while appropriately adjusting for other potential covariates. Methods. The present study employed a cohort design and utilized data from the Surveillance, Epidemiology, and End Results (SEER) program spanning from 2010 to 2015. The study population consisted of 683,336 individuals who were diagnosed with breast cancer (referred to as BC). Various covariates were assessed at baseline, including age, sex, race, marital status, CS tumor size, laterality, radiation, chemotherapy, months from diagnosis to treatment, breast subtype, AJCC 7th edition (2010–2015), and combined summary stage (2004+). The primary objective of this study was to investigate the association between ER, PR, HER2, ER−/PR+ status, and the risk of developing BC-LuC. Logistic regression analysis was employed to assess this association. Furthermore, multivariable Cox regression analyses were conducted to calculate adjusted hazard ratios (HRs) along with their respective 95% confidence intervals (CIs). Kaplan–Meier plots and log-rank tests were utilized to estimate the outcomes, specifically overall survival (OS), disease-specific survival (DSS), and metastasis. Results. The average age of 198,972 selected participants was 59.8 ± 13.1 years, and about 99.3% of them were female. Result of fully adjusted binary logistic regression showed PR+ and HER2+ were positively associated with lower risk BC-LuC after adjusting confounders (ORs = 0.84, 95% CI: 0.73–0.96, p = 0.011 and ORs = 0.83, 95% CI: 0.72–0.96, p = 0.012, respectively). ER+ and ER−/PR+ were detected no significant relationship with BC-LuC (ORs = 1.03, 95% CI: 0.87–1.22, p = 0.718 and ORs = 1.02, 95% CI: 0.61–1.72, p = 0.936, respectively). In subgroups analyses, the results remain stable. Multivariable Cox regression showed that BC-LuC patients with ER and PR were significantly associated with OS and DSS. However, ER, PR, HER2, and ER−/PR+ were significantly associated with OS and DSS in breast cancer patients. The relationship between ER, PR, HER2, and ER−/PR+ and metastasis in breast cancer patients was different. Conclusion. The results of this study indicated a potential correlation between PR- and HER2- status and a risk of developing BC-LuC. Furthermore, it appears that the prognosis of BC-LuC may be influenced by the presence of ER+ and PR+. Therefore, additional research is warranted to fully investigate and validate this association.